2022
DOI: 10.1186/s43058-022-00336-9
|View full text |Cite
|
Sign up to set email alerts
|

Readiness as a precursor of early implementation outcomes: an exploratory study in specialty clinics

Abstract: Background Readiness has been identified as an essential precursor of successful implementation. However, evidence supporting its value is sparse. Empirical studies exploring the relationship between the application of readiness interventions, readiness levels, and implementation outcomes are lacking. The purpose of this study was twofold: (1) to evaluate the effectiveness of a readiness intervention (based on increases in readiness levels, changes in early implementation outcomes (i.e., accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Readiness assessments typically involve determining if health system members understand the tasks required to implement new policies or programmes, assessing availability of required resources, and identifying favourable conditions for implementation 34 35. High levels of readiness are associated with increased acceptability and intent to adopt new policies or programmes, resulting in more successful implementation 36 37. In our study, a readiness survey will identify the Ethiopian health system’s readiness and capacity to scale up the LAUNCH intervention and identify points of lower readiness, where additional support or change management might be needed prior to implementation of a scaled up LAUNCH intervention or other community-based programmes for newborn health.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Readiness assessments typically involve determining if health system members understand the tasks required to implement new policies or programmes, assessing availability of required resources, and identifying favourable conditions for implementation 34 35. High levels of readiness are associated with increased acceptability and intent to adopt new policies or programmes, resulting in more successful implementation 36 37. In our study, a readiness survey will identify the Ethiopian health system’s readiness and capacity to scale up the LAUNCH intervention and identify points of lower readiness, where additional support or change management might be needed prior to implementation of a scaled up LAUNCH intervention or other community-based programmes for newborn health.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The question can be raised if implementation be started at all if like in M2 at baseline 50% of participants scored in quadrant I "Low Acceptability and low Readiness" while only 26% of M2 scored in the quadrant "High acceptability and high readiness". Another study also found a high correlation between readiness and implementation outcomes and suggested that readiness is a precursor of early implementation outcomes like ACC, APP and FEAS and an essential step in the preimplementation process (11). These authors warned against implementing a service in an organization receiving a low appropriateness score without engaging in a process to improve readiness.…”
Section: Implementation Outcomes and Readiness Were Correlatedmentioning
confidence: 99%
“…The concept of readiness has been shown to be highly correlated with early implementation outcomes like ACC, APP and FEAS, but there does not seem to be a simple linear relationship between these outcomes (11). While a program may be found acceptable by the stakeholders and appropriate for a given setting, it may not be feasible typically due to lack of resources or competence of providers.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the implementation phase was shortened from 12 to 8 months due to the advent of the COVID-19 pandemic. Briefly, the planning phase (described elsewhere 15 ) aimed to increase implementation readiness through an evidence-informed systematic process involving participation in trainings, development of implementation teams, readiness assessments and action plans, and development of the needed implementation infrastructure for CMM (e.g., tailored CMM workflows).…”
Section: Clinic Recruitment Expectations and Implementationmentioning
confidence: 99%